Research on Big Data, VGI, and the Tourism and Hospitality Sector: Concepts, Methods, and Geographies - Ferreira, Daniela (2020)
The emergence of new data sources with high volume, velocity and variety has changed the market and consumption trends, including within the tourism industry. The tourism industry faces several challenges when using big data and volunteered geographic information (VGI) to develop new services. Managers need new capabilities to exploit this newly available information and to understand the possibilities that it has created. To give an overview of relevant academic knowledge, this chapter investigates academic research big data, volunteered geographic information, and the tourism and hospitality sector. It tracks the number of relevant publications and reviews the main concepts and research methods used in them. The results of this study give new insights on the main themes within scientific research on this topic, inform critical perspectives on the subject, and identify gaps in the current literature.